Improving translational research in sex-specific effects of comorbidities and risk factors in ischaemic heart disease and cardioprotection: position paper and recommendations of the ESC Working Group on Cellular Biology of the Heart - Perrino,C; Ferdinandy,P; Bøtker,HE; Brundel,BJJM; Collins,P; Davidson,SM; den,Ruijter HM; Engel,FB; Gerdts,E; Girao,H; Gyöngyösi,M; Hausenloy,DJ; et al. (Cardiovascular Research, 2021)
Ischaemic heart disease (IHD) is a complex disorder and a leading cause of death and morbidity in both men and women. Sex, however, affects several aspects of IHD, including pathophysiology, incidence, clinical presentation, diagnosis as well as treatment and outcome. Several diseases or risk factors frequently associated with IHD can modify cellular signalling cascades, thus affecting ischaemia/reperfusion injury as well as responses to cardioprotective interventions. Importantly, the prevalence and impact of risk factors and several comorbidities differ between males and females, and their effects on IHD development and prognosis might differ according to sex. The cellular and molecular mechanisms underlying these differences are still poorly understood, and their identification might have important translational implications in the prediction or prevention of risk of IHD in men and women. Despite this, most experimental studies on IHD are still undertaken in animal models in the absence of risk factors and comorbidities, and assessment of potential sex-specific differences are largely missing. This ESC WG Position Paper will discuss: (i) the importance of sex as a biological variable in cardiovascular research, (ii) major biological mechanisms underlying sex-related differences relevant to IHD risk factors and comorbidities, (iii) prospects and pitfalls of preclinical models to investigate these associations, and finally (iv) will provide recommendations to guide future research. Although gender differences also affect IHD risk in the clinical setting, they will not be discussed in detail here.